Financial whirlpools a systems story of the great global recession - Higgins, Karen L. (Elsevier, AP, Academic Press in an imprint of Elsevier, 2013)
"How do economists reconcile their expertise with their failures to predict and manage the 2008 financial crisis? This book goes a long way toward an answer by using systems theory to reveal the complex interdependence of factors and forces behind the crisis. In her fully integrated view of the economy, how it works, and how the economic crisis burst, Karen Higgins combines human psychology, cultural values, and belief formation with descriptions of the ways banks and markets succeed and fail"--Amazon.com.